A Framework for Articulating and Measuring Individual Learning Outcomes from Participation in Citizen Science. (28th August 2018) - Phillips, Tina; Porticella, Norman; Constas, Mark; Bonney, Rick
Since first being introduced in the mid 1990s, the term "citizen science"—the intentional engagement of the public in scientific research—has seen phenomenal growth as measured by the number of projects developed, people involved, and articles published. In addition to contributing to scientific knowledge, many citizen science projects attempt to achieve learning outcomes among their participants, however, little guidance is available for practitioners regarding the types of learning that can be supported through citizen science or the measuring of learning outcomes. This study provides empirical data to understand how intended learning outcomes first described by the informal science education field have been employed and measured within the citizen science field. We also present a framework for describing learning outcomes that should help citizen science practitioners, researchers, and evaluators in designing projects and in studying and evaluating their impacts. This is a first step in building evaluation capacity across the field of citizen science.